Pengawasan Rencana Keselamatan Konstruksi Menggunakan Metode Hazard dan Risk Control pada Pemancangan Jembatan Sebulu Tahap 1: Supervision of Construction Safety Plans Using Hazard and Risk Control Methods in the Erection of the Sebulu Bridge Phase 1 - Noor, Rusandi; Husna, Yusrika Asmaul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Sebulu Bridge Construction Project in Kutai Kartanegara Regency, East Kalimantan, aims to enhance interregional connectivity and facilitate the mobility of people and logistics distribution. This community service activity has two main objectives: to understand the methods of implementing Occupational Health and Safety (OHS) in the construction project, and to identify potential hazards that may cause work accidents through a hazard identification approach. The methods used in this activity include direct field observation, interviews with project implementers, and hazard analysis based on the types of work performed. The results indicate that the highest risks originate from working at heights, operating heavy equipment, and exposure to hazardous materials. OHS implementation measures include using personal protective equipment (PPE), periodic safety training, and intensive supervision at the project site. The discussion reveals that while the implementation of OHS has been relatively effective, there are still challenges related to worker discipline and limited supervisory resources. Therefore, increased supervision, stricter enforcement of OHS regulations, and regular evaluations are required to improve the effectiveness of safety systems on site.